(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article highlights lesser-known masterpieces of English literature that deserve recognition and appreciation. It explores the diverse themes, captivating narratives, and thought-provoking elements present in these hidden gems, inviting readers to embark on a literary journey of discovery and expand their understanding of the breadth and depth of English literature.